The Role of Self-Efficacy and Injunctive Norms in Helping Older Adults Decide to Stay Home During the COVID-19 Pandemic - Macy, Jonathan T.; Owens, Christopher; Mullis, Kristina; Middlestadt, Susan E. (Frontiers in Public Health, 2021)
Purpose: Because older adults are at elevated risk of COVID-19-related adverse health outcomes, and staying at home is an effective strategy to avoid unnecessary exposures, the current formative study used the Reasoned Action Approach (RAA) to identify the beliefs underlying older adults’ decision to stay home for the next month. Methods: The participants (weighted n=206, age 65-94) for the current study were selected from a nationally representative online survey of US adults from April 10-20, 2020. We used multiple linear regression to estimate the relative contribution of the four RAA global constructs (instrumental attitude, injunctive norm, descriptive norm, and self-efficacy) in explaining intention to stay home after controlling for demographic covariates. We also conducted a content analysis to identify beliefs about advantages, disadvantages, and facilitators of staying home. Results: After controlling for demographic characteristics, injunctive norm (b=0.208; SE=0.059; B=.213, p<.01) and self-efficacy (b=0.532; SE=0.058; B=.537, p<.001) showed statistically significant independent associations with intention to stay home. The specific beliefs underlying the decision to stay home spanned across health and wellness dimensions and suggested interpersonal, mental health, and leisure/recreational facilitators. Conclusions: These findings suggest three public health intervention targets. First, self-efficacy building interventions could enhance older adults’ perceptions of their ability to stay home to avoid unnecessary exposures. Second, health communication messages to address injunctive norm could emphasize that people important to older adults think they should stay home. Third, for the youngest of the older adults, health communication messages could emphasize the advantages of staying home.